Rancang Bangun Sistem Informasi Manajemen Negeri Tawiri Berbasis Web - Victor Febian Puturuhu (P3M Politeknik Negeri Ambon, 2026)
This research is motivated by service activities for the community, where the current condition arises during data collection. The residents of Tawiri country face several obstacles, such as the process. Population data recording is still manual or paper-based, resulting in the accumulation of paper in the State Government Office’s archive room. Previous research used as a reference is Riady, I., & Hasugian,. (2020) Information Systems Community Services at the Tanimulya Village Office. Theories used in this research is carried out by Prasetiyo and R.P Daniawaty, Indonesian Computer University In 2020, the definition of application according to Eka Noviansyah (2008:4) Data Flow Diagram. According to H.M. Jogiyanto (1989:700), the methodology to be used in this research is Communication, which includes literature studies, data collection, Observations, interviews, and field reviews and documentation. Next stage, namely analysis, to study the flow in the service stages, a design is carried out for the new system to be created. The next stage is Construction, which creates a system or application according to the design. The next stage is testing the program that has been created to test whether there are still problems in testing If there are still problems, they will be repaired immediately. The last stage is the implementation stage, namely running the application so that it can be used by the people of Tawiri Country Keywords: Web-based, Tawiri State, Management Information System